Electronic Archiving and Data Protection from Crises: An Applied Study Faculty of Arts and Education, Sabratha University (Al-Farooq Journal of Sciences, 2026)
This study aimed to examine the role of electronic archives in protecting data during crises through an applied study at the Faculty of Arts, Sabratha University. It also sought to identify the current status of electronic archiving systems, evaluate the effectiveness of data protection measures against loss, damage, or unauthorized access during emergencies, identify the major challenges facing electronic archive management, and propose mechanisms to strengthen information security and ensure business continuity.The study adopted a descriptive analytical approach and used a questionnaire as the primary data collection instrument. The study sample consisted of faculty members and administrative staff at the Faculty of Arts. The findings indicated a growing interest in implementing electronic archiving systems; however, several challenges remain, including limitations in technical infrastructure, backup policies, information security practices, and continuous staff training. The results also demonstrated that effective data protection measures significantly enhance business continuity and reduce the risks of data loss during crises.The study recommends improving digital infrastructure, adopting comprehensive information security policies, implementing regular training programs for employees, establishing reliable backup and disaster recovery systems, and developing crisis management plans to ensure the protection of electronic archives and institutional data.